Serum Lipoprotein Profile Is Associated With Protective Effects of Oral Contraceptive Use on Multiple Sclerosis Severity: A Cross-Sectional Study - Sena, Armando; Macedo, Ana; Ferret-Sena, Véronique; Capela, Carlos; Pedrosa, Rui (Frontiers in Neurology, 2019)
Background: The mechanisms underlying the influence of sex hormones in multiple sclerosis (MS) are uncertain. Sex steroids interact with cholesterol metabolism and the serum lipid profile has been associated with the severity of the disease. We hypothesized that the putative associations between lipoprotein metabolism and MS could be modulated by sex steroids exposure. The aim of this study was to investigate whether oral contraceptives (OC) use changes the lipoprotein profile associated with disability in patients with multiple sclerosis. Methods: Clinical data was collected from 133 relapsing-remitting multiple sclerosis (RRMS) women with a mean of 6.5 years of disease duration and prior to the start of disease-modifying therapies. Patients who were using OC after disease onset (DO) (OC+, n=57) were compared to those who never used OC or discontinued its intake before DO (OC-, n=76). In both cohorts of subjects, the associations between the apolipoprotein E (ApoE) polymorphism, and plasma lipid levels, and the annualized relapse rate (RR), the Expanded Disability Status Score (EDSS) and the Multiple Sclerosis Severity Score (MSSS) were evaluated using a hierarchic multiple regression analysis after adjustment for confounders. Results: Higher low density lipoprotein (LDL) levels were associated with higher EDSS (p=0.010) and MSSS (p=0.024) in the whole studied cohort. In E3/E3 phenotype carriers (73.7%), EDSS and MSSS were lower in OC+ in comparison with OC- subgroup of patients (p< 0.01). LDL and total cholesterol were associated with EDSS (p=0.005 and p=0.041, respectively), and LDL and the triglyceride/high density lipoprotein ratio with MSSS (p=0.029 and p=0.016, respectively) in OC+ patients. In OC- subgroup of patients, ApoE levels were associated with EDSS (p=0.012) and MSSS (p=0.025). No significant interactions between the lipid variables or OC use and RR were observed. Conclusions: Serum lipid profile is associated with protective effects of OC use on disability of RRMS patients. Lipoprotein metabolism may be involved in the modulatory effects of sex steroids on the severity of the disease.